Analysis of the Temon Bayi Tradition from the Perspective of ʿUrf - Muh. Baehaqi; Tanti Trisnawati; Braham Maya Baratullah (Yayasan Azhar Amanaa Yogyakarta, 2025)
The adoption of children in Indonesia is not a new phenomenon. In Islamic jurisprudence (fiqh), the adoption of a child is referred to as tabanni. The practice of adopting children has existed since the era of Jahiliyyah (pre-Islamic ignorance). One of the customary traditions that gives rise to legal events related to child adoption is the Temon Bayi tradition. The Temon Bayi tradition is a customary practice carried out when a mother gives birth to two babies in succession, both of whom pass away. When she gives birth to a third child, according to this tradition, the third child must be “entrusted” to a traditional birth attendant (dukun bayi), and symbolically becomes the child of the birth attendant. Therefore, this research aims to examine how the practice is carried out and how ‘urf (customary law) views the Temon Bayi tradition. This research is a qualitative study using field research methods and a normative-sociological approach. Based on the findings, it is concluded that the Temon Bayi tradition process includes: a symbolic entrustment contract (akad) to a non-family member, naming of the child, a thanksgiving ceremony (syukuran), and a redemption ritual (penebusan) once the child reaches puberty. This tradition is a part of valid custom (al-‘urf al-shahih) in Islam because it does not contradict sharia, preserves lineage (nasab), and contains elements of public benefit (maslahah). The tradition reflects al-‘urf al-lafzi in terms of its scope and is categorized as al-‘urf al-khas in terms of its object.